Roving pharmacies: Modelling the dispersion of pharmaceutical contamination in estuaries. (August 2020) - Fonseca, Vanessa F.; Reis-Santos, Patrick; Duarte, Bernardo; Cabral, Henrique N.; Caçador, M. Isabel; Vaz, Nuno; Dias, João M.; Pais, Miguel P.
Highlights: Modeling pharmaceuticals transport in an estuary under different freshwater flows. Particles source and trajectories up to 10 days used as proxy to exposure potential. Modeled exposure potential depicted previously identified pharmaceutical hotspots. Vulnerable areas largely composed of intertidal soft substratum and salt marshes. Framework allowed identification of priority areas for monitoring pharmaceuticals. Abstract: We characterized the transport pathways of pharmaceuticals released from wastewater outfalls in one of Europe's largest estuarine systems (Tagus estuary, Portugal), to identify areas of ecological relevance prone to environmental degradation due to increased exposure to these emerging contaminants. Particle source, Lagrangian trajectories and arrivals over time (1, 6, and 10 days) were used as a proxy to determine the exposure potential and vulnerability of different habitats to an array of pharmaceuticals with different environmental degradation rates and half-lives. Then, exposure potential was combined with information on sensitive habitats to identify vulnerable areas in the estuary. Three different freshwater inflow scenarios were considered simulating Medium flow, No flow and flood conditions (High flow). Model results for areas with higher particle density were concordant with concentration hotspots of pharmaceuticals. Higher potential exposure in a larger area of the estuary was observed for the High freshwater flow; yet reduced particles export to adjacent coastal areas highlights the potential of estuaries and bays as particle sinks. In all modeled scenarios, vulnerable areas were predominantly located in the southern bays up to day 6, and later in eastern areas, which include a nature reserve. These areas are largely composed of intertidal soft substratum and salt marshes habitats, and thus warrant prioritization for monitoring and risk assessment of pharmaceuticals exposure in the Tagus estuary due to the higher risk of exposure of a wealth of vertebrate and invertebrate species that use them. This framework allowed the identification of vulnerable areas to pharmaceutical contamination and can be a valuable instrument to plan the location for wastewater treatment plants (WWTPs) in estuaries and coastal areas.